Analysis of ciliary status via G-protein-coupled receptors localized on primary cilia. (6th July 2020) - Kobayashi, Yuki; Hamamoto, Akie; Saito, Yumiko
Abstract: G-protein-coupled receptors (GPCRs) comprise the largest and most diverse cell surface receptor family, with more than 800 known GPCRs identified in the human genome. Binding of an extracellular cue to a GPCR results in intracellular G protein activation, after which a sequence of events, can be amplified and optimized by selective binding partners and downstream effectors in spatially discrete cellular environments. Because GPCRs are widely expressed in the body, they help to regulate an incredible range of physiological processes from sensation to growth to hormone responses. Indeed, it is estimated that ∼ 30% of all clinically approved drugs act by binding to GPCRs. The primary cilium is a sensory organelle composed of a microtubule axoneme that extends from the basal body. The ciliary membrane is highly enriched in specific signaling components, allowing the primary cilium to efficiently convey signaling cascades in a highly ordered microenvironment. Recent data demonstrated that a limited number of non-olfactory GPCRs, including somatostatin receptor 3 and melanin-concentrating hormone receptor 1 (MCHR1), are selectively localized to cilia on several mammalian cell types including neuronal cells. Utilizing cilia-specific cell biological and molecular biological approaches, evidence has accumulated to support the biological importance of ciliary GPCR signaling followed by cilia structural changes. Thus, cilia are now considered a unique sensory platform for integration of GPCR signaling toward juxtaposed cytoplasmic structures. Herein, we review ciliary GPCRs and focus on a novel role of MCHR1 in ciliary length control that will impact ciliary signaling capacity and neuronal function.